Diagnostic Problem in Systemic Lupus Erythematosus: Ana Test and Other Immunologic Test - Mahayasa, I Made Arya Yogiswara; Dewi, Ayu Santia; Tilana, Febry Gilang; Roliskana, Shafalyn Kalila; Kusuma, I Gusti Bagus Surya Ari; Salsabila, Lale Sirin Rifdah; Wardhani, Indah Sapta; Habib, Philip (Jurnal Biologi Tropis, 2024)
Systemic Lupus Erythematosus (SLE) is a complex chronic autoimmune disease that can affect multiple organ systems, with diverse clinical symptoms, disease course and prognosis. This study aims to evaluate the role of antinuclear antibody (ANA) tests and other immunologic tests in supporting the diagnosis of SLE, given the challenges in differentiating SLE from other autoimmune diseases. The method used was a literature review of relevant literature obtained through several databases, such as PubMed, Google Scholar, and ProQuest, which analyzed the accuracy and limitations of ANA tests and other immunological tests in supporting the diagnosis of SLE. The results show that the ANA test has high sensitivity but limited specificity, as positive ANA results can also be found in other autoimmune conditions or even in healthy individuals. Therefore, interpretation of ANA results should be done in the appropriate clinical context to optimize its diagnostic utility. In conclusion, ANA testing plays an important role in the evaluation of SLE and other ANA-related diseases, but should be combined with clinical evaluation and additional investigations to confirm or exclude the diagnosis.